UPAYA MENINGKATKAN KETERAMPILAN BERHITUNG PADA ANAK USIA DINI DI RA NUR QOMARIAH JAMPANGTENGAH SUKABUMI - Irma Muti; Jimatul Arrobi; Dede Risnawati; Dini Alwaliyah; Hani Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine efforts to improve early childhood numeracy skills at RA Nur Qomariah Jampangtengah, Sukabumi. The research employed a qualitative descriptive approach to gain an in-depth understanding of the processes, strategies, and factors influencing children's numeracy development. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results indicate that efforts to improve numeracy skills are carried out by optimizing internal, external, and environmental factors. These efforts include the use of varied play-based learning methods, the utilization of concrete learning media, enhancement of children’s concentration and learning interest, and parental involvement in providing stimulation at home. The implementation of these strategies resulted in improvements in children’s ability to recognize number symbols, sequence numbers, understand basic addition, and relate quantities to numerical symbols. In conclusion, improving early childhood numeracy skills requires a comprehensive and integrated approach that considers children’s developmental characteristics. Collaboration between teachers, appropriate teaching methods, and support from both family and school environments plays a crucial role in optimizing children’s numeracy development.